Can Africa claim the 21st century? - World Bank (Washington, DC, 2000)
"'Can Africa claim the 21st century?' is a product of the growing collaboration among some of the main institutions involved in African development: the African Development Bank, African Economic Research Consortium, GlobalCoalition for Africa, United Nations Economic Commission for Africa, and World Bank. More than 50 scholars, policymakers, and development practitioners- predominantly African - appraised the region's development at the start of the new century and articulated a road map for the future"
Bibliography: p. 259-278
Keywords: Since 1900; Social change -- Africa; Poverty -- Africa; Equality -- Africa; Infrastructure (Economics); Aid coordination; Economic and social development; Africa; Africa South of Sahara; Poverty Alleviation; Good governance